Research and development of a laparoscopic surgical device for ligating endless organs based on a flexible structure. (31st October 2017) - Zhu, Rui; Yamamoto, Ikuo; Lawn, Murray John; Hashimoto, Yasumasa; Nagayasu, Takeshi; Yamasaki, Naoya; Matsumoto, Keitaro
Abstract: While laparoscopic surgery has become increasingly widely used, many laparoscopic procedures are time-consuming and difficult to accomplish compared to open surgery. One such procedure is the ligation of endless organs. In this paper, the development and prototyping of a laparoscopic instrument that could significantly increase the efficiency of laparoscopic ligation is outlined. The mechanism is based on a snake-like flexible structure which is actuated by control wires. A simple simulation was carried out by both experienced surgical staff as well as non-surgical persons to confirm the effectiveness of the proposed mechanism.